2018
DOI: 10.1891/1945-8959.17.1.97
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Assessment of Narratives: A Bilingual Study

Abstract: This study applied the dynamic assessment (DA) of narratives in a bilingual Spanish- and English-speaking early elementary population. We examined transfer and change in narrative performance within and across languages after mediated learning experience (MLE) in Spanish or English. Sixty-eight bilingual children were randomized to two groups: Spanish (n = 24) or English mediation (n = 25), while a control group (n = 19) participated in regular academic activities. The MLE Spanish and English groups participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 105 publications
3
3
0
Order By: Relevance
“…This is suggestive of possible cross-linguistic transfer of narrative language skills from Spanish to English. Results replicate previous work (Fiestas & Peña, 2018) in which children demonstrated transfer of narrative skills to the nontargeted language following MLE in either Spanish or English. A summary of these (and those discussed later) main effects and interaction effects is shown in Table 3.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…This is suggestive of possible cross-linguistic transfer of narrative language skills from Spanish to English. Results replicate previous work (Fiestas & Peña, 2018) in which children demonstrated transfer of narrative skills to the nontargeted language following MLE in either Spanish or English. A summary of these (and those discussed later) main effects and interaction effects is shown in Table 3.…”
Section: Resultssupporting
confidence: 86%
“…Children scored higher on Spanish narratives (M = 6.75) than on English (M = 3.43). This aligns with previous work (e.g., Fiestas & Peña, 2018;Spencer et al, 2019) where narrative language skills of ELLs in early grades are stronger in L1 (Spanish).…”
Section: Topics In Language Disorders/october-december 2021supporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, researchers began to explore the interplay between stories (storytelling) and children's narrative abilities by focusing on bilinguals or comparing monolinguals and bilinguals (MacLeod & Pesco, 2023;Fiestas & Peña, 2018;Young, 2015). For example, found that English-Spanish bilingual children can significantly improve vocabulary in both languages while developing overall story structure at different levels.…”
Section: Narrative Theory and Bilingual Storytelling Curriculummentioning
confidence: 99%